Fintech Remittance Syariah : The Solution of Collection Ziswaf Overseas - Pati, Umi Khaerah; Tejomurti, Kukuh; Pujiyono, Pujiyono; Pranoto, Pranoto (Brawijaya Law Journal : Journal of Legal Studies, 2021)
Indonesian National Amil Zakat Board (BAZNAS) has collaborated with the largest and popular Indonesian payment gateways, e-commerce and crowdfunding fintechs such as ovo, Gojek, Kitabisa.com, Tokopedia.com etc. to optimize the collection of Islamic social funds like  Zakah,  infaq (charity spending), waqf (endowment) and sadaqah (voluntary charity) or usually called ZISWAF by depositing Rupiah currency into the e-wallet platform. However, fundraising cross-border ZISWAF stated in Article 16 Law No. 23/2011 on Zakat Management is carried out by Baznas by forming UPZ representatives of the Republic of Indonesia abroad.  The power of fintech that might be operated on global scale can be an alternative for ZISWAF international friendly transfers. Based on the Islamic Finance News (IFN) report, as many as 142 Islamic fintechs are available worldwide. Islamic FinTech offers the opportunity to become more applicable to a global Muslims. This article is a normative economic analysis on the basis of secondary data, this study found that the potential for raising ZISWAF funds across several countries is very large especially in countries with many immigrants from Indonesia through international types of fintech services such as remittances and payments that has allowed or collaborated with Bank Indonesia.